2021
DOI: 10.1088/1755-1315/653/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of lime and NPK fertilizer on shallot production in peat soil

Abstract: High acidity level and low nutrient availability are the most challenging factors of shallot production in peat soils. The purpose of this study was to find out the best lime material and the level of NPK fertilizer on shallot production in peat soil in Central Borneo, Indonesia. The experiment used was a Split Plot Design with three replications. The main plot was three types of lime material: 3 t ha−1 dolomite, 3 t ha−1 agriculture limestone and 1.5 t ha−1 calcium hydroxide. The subplots were ten combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Increasing soil pH in organic soils due to dolomite application has been well studied. A pot study reported that the addition of lime doses 7.5 g kg -1 to peat soils increased soil pH from 4.14 to 5.52 (Nurhayati et al, 2014), and 3 t ha -1 dolomite increased peat soil pH from 3.7 to 4.3 (Sopha et al, 2021). The increase in soil pH was linear with the level of dolomite (Lestari et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing soil pH in organic soils due to dolomite application has been well studied. A pot study reported that the addition of lime doses 7.5 g kg -1 to peat soils increased soil pH from 4.14 to 5.52 (Nurhayati et al, 2014), and 3 t ha -1 dolomite increased peat soil pH from 3.7 to 4.3 (Sopha et al, 2021). The increase in soil pH was linear with the level of dolomite (Lestari et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The treatment without phosphorus fertilizer addition (P1, P7) had a high concentration of P, which might be due to the high concentration of total phosphorus in the soil. Lime application increased soil pH, improved phosphorus availability, and increased the available P (Sopha et al, 2021). Phosphorus is an immobile element, and the soil analysis result is highly influenced by the sampling method during the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…other micronutrients and result in lower yields obtained. According to Sopha et al (2020), insufficient nitrogen supply keeps onions growing, but continues to reduce bulb size and marketable tuber yields. P deficiency in shallots will reduce root and leaf growth, tuber size and yield, but will further support optimal aging.…”
Section: Resultsmentioning
confidence: 99%
“…The use of lime only increased the Ca 2+ , pH, and the indigenous available P of peat [47] , while the application of manure added nutrients to the peat so that the growth and yield of liberica coffee increased significantly. Maftu'ah et al [48] also reported that using manure in combination with mineral fertilizers increased the number and weight of chilly fruits on degraded peatland. Meanwhile, Salim et al [40] showed that the use of manure of 2.5 t/hm 2 in horticultural cultivation, besides increasing crop production, can also maintain the chemical properties of peat.…”
Section: Effect Of Amendments On Growth Productivity and Quality Of Peatmentioning
confidence: 98%